Civil Society Participation Model: Forest and Land Fire Prevention Policy in Jambi Province - Sundari, Cici; Purnomo, Eko Priyo; Fathani, Aqil Teguh (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
This study aimed to analyze the factors that influence community participation in forest and land fire prevention. The focus of this research is on Jambi Province. This study used a qualitative descriptive method, and the data sources were obtained through interviews, online media, online news, and research-related journals. Data analysis used the NVivo 12 plus data processing application, a qualitative document analysis tool with the help of a computer. They are easy to use and can process words and explore word frequency, attributes, and cases from big data, generating factor categories in journalistic and research applications related to the research topic. The results showed that the government made a strategy to encourage community participation in environmental management cooperation, especially in overcoming the problem of forest and land fires in Jambi Province. Informal reactions from the community can be seen through the government’s policy to create a Fire Care Group program that is motivated by community aspirations for forest and land fires. The government formed the Fire Care Group to reduce the number of forest and land fires.